Management of Inclusive Education Services in School Through Self Awareness, Motivation, and Self Efficiency - Endro Wahyuno; Asep Sunandar; Ediyanto Ediyanto; Risa Safira Ramadhani; Bella Dina Fitrasari (Journal of Disruptive Learning Innovation (JODLI), 2021)
This study aims to analyze the management of inclusive education services in schools through self-awareness, motivation, and self-efficacy. This study uses a qualitative research method with a case study approach through interviews with principals and teachers at inclusive schools in Malang. Based on the study results, it is known that when school members have self-awareness and have high motivation to teach children with special needs, self-efficacy grows in teachers to provide inclusive education services that are according to crew needs. Management strengthening in schools that implement inclusive education is obtained through socialization, training, and policy provision.